다꾸지 기법 및 신경망을 이용하여 코팅공구의 성능예측 연구 - 최광진(Choi Gwang Jin); 이위로(Lee Wi Ro); 최석우(Choi Suk Woo); 백영남(Paik Young Nam) (Biuletyn Uniejowski, 2003)
In this study, the prediction on the quality of tools after coating process has been investigated. Under different coating conditions, cutting resistances have been obtained and analyzed with a tool dynamometer to provide optimized coating conditions. The optimized coating conditions Lhave been computed with the most effective factors found by S/N ratio of Taguchi method. To evaluate the influence of the factors on cutting efficiency through the minimum of number of experiment times, the way of neural network design using Taguchi method has been employed.